Aprendizagem da arte por meio da modelagem em argila: uma análise do processo metodológico da prática no âmbito escolar - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
This research refers to the pedagogical analysis of a clay modeling practice workshop, held at Escola Estadual Machado de Assis, with students from the 3rd year of elementary school I. Its intention is to discuss the modeling process carried out by the students, through methodological observation of experience. In this way, the general objective is to highlight theoretical knowledge related to the teaching of ceramic art, emphasizing the practice of modeling in the school environment and using action research as a methodology. The nature of this research was qualitative, containing as an experimental and practical method the development of a clay modeling practice workshop. To achieve this proposal, interdisciplinary theoretical contributions are applied, such as teaching arts, history, culture and heritage education. The experience report is also used in order to cover issues such as the need for an adequate place and materials in schools for practice and the relevance of the triangular approach linked to the teaching of the arts, using the process notebook as a source of record. Through this workshop, we sought to provide opportunities for initiation, the practice of modeling and production for students in the initial years.
Keywords: LINGUISTICA, LETRAS E ARTES: ARTES: ARTES PLASTICAS: CERAMICA; Argila; Arte Educação; Cerâmica; Modelagem